Wavelength-Dependent Three-Dimensional Volumetric Optical Vortices Modulation Based on Metasurface - Jinjin Jin; Xiong Li; Mingbo Pu; Xiaoliang Ma; Xiangang Luo (IEEE Photonics Journal, 2018)
The emergence of the metasurface has spawned an ultrathin, compact, and planner way to generate the orbital angular momentum (OAM) beam array. Several types of OAM beam array generators based on the metasurface have been reported, however, most of them only performed at the certain wavelength for lack of the wavelength-dependent modulation, which restricted the flexibility and capacity of the generators. Here, we propose a single-layered metasurface to realize the generation of the wavelength-dependent three-dimensional (3-D) volumetric vortex beam array. The metasurface is composed by two different nanoantennas, which shows the distinct properties of wavelength selectivity and wavelength-dependent phase modulation. By employing such properties, 3-D volumetric vortex beams operating at different wavelengths can be multiplexed. Our design may facilitate the development of the optical multiplexing, and the wavelength-dependent control of the OAM light will improve the capacity and the security of the optical information.